PENGGARAPAN LAHAN OLEH MASYARAKAT DI SUAKA MARGASATWA PALIYAN KABUPATEN GUNUNGKIDUL DAERAH ISTIMEWA YOGYAKARTA - , Bisro Syabani; , Prof. Ir. Bakti Setiawan, M.A.,Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Paliyan Wildlife Sanctuary is a legal protected area of 434.6 hectares, located in Yogyakarta Special Region. At the time this area is stated as wildlife sanctuary, there were 2,000 illegal land tillers of the adjacent villages (Karangduwet, Karangasem, Kepek and Jetis). At the moment, this problem is still exist. Community development program of the adjacent villages is conducted by Yogyakarta KSDA Office and Mitsui Sumitomo Insurance Co., Ltd to reduce local community dependency on forest especially activity of tilling the land. The research aimed to map out illegal utilization of the land by local community in Paliyan Wildlife Sanctuary area, to identify the affected factors and to study the community development activities of the adjacent area to reduce society dependency of Paliyan Wildlife Sanctuary. The research used inductive approach and qualitative descriptive method. The research shows that illegal land utilization at the Paliyan Forest (which now become Paliyan Wildlife Sanctuary) has started since 1950âs. The encourage factors of the community to do working field at the wildlife sanctuary are: to fulfill economyâs needs, the lack of field ownership, easy access, history/ cultural aspect, area authority policy, and the plant condition rehabilitation. The encourage factors to end the society work the field at the Paliyan Wildlife Sanctuary area are: the reducing working plant productivity, field rehabilitation activities success, difficult access, and also the socialization and counseling activities. Community empowerment program developed by the Yogyakarta KSDA Office and Mitsui Sumitomo Co., Ltd program to reduce society dependency on the Paliyan Wildlife Sanctuary area and to prompt the field worker pull out of the area has not yet maximum. The amount of the worker, field width, damage areas intensity, and the society income is relatively constant since the program started two years ago. The biggest benefit of this community empowerment is the knowledge and capacity enhancement especially in agriculture.